Field Study of Roads Quality In Saudi Arabia: دراسة ميدانية لجودة الطرق في المملكة العربية السعودية - Abdullah Jarbo M. Albnnaqi, Mohamed Ahmed Aichouni (Journal of engineering sciences and information technology, 2020)
Roads networks are considered as one of the major components of the economical infrastructure in any country in the world. Roads play an important role in the sustainable economic development of countries such as Saudi Arabia. Roads` quality is considered to be one of the most important indicators of quality of life and economic competitiveness. Therefore, it is very important for government and economic agencies such as ministries and municipalities to strive to maintain the road network with appropriate levels of quality and maintain safety standards. The present paper aims to conduct a field study of road quality in one of the most important customs border Centers in the Kingdom. This study can be considered of major importance to the Kingdom since it is closely related to the Saudi Vision 2030, the National Transformation Program, and the Quality of Life Program. The research used the field survey method to collect data on types of road paving defects, determine the level of road quality, and identify the most important factors leading to the deterioration of the road`s quality. Quality tools such as Check Sheet, Pareto Analysis and statistical methods were used to collect real field data and analyze them. Micro PAVER 5.2 Software was used to perform data analysis in order to assess the level of road quality according to the approved international indicators, and to predict the level of deterioration that will reach the road in future years if maintenance operations are not carried out in time.